The Paris System: achievement of a standardized diagnostic reporting system for urine cytology. Issue 10 (October 2018) - Snow, Justin T.; McIntire, Patrick J.; Siddiqui, Momin T.
Abstract: Urinary tract cytology is a common diagnostic test used in the initial work up of bladder cancer. Since its inception as an utilizable diagnostic technique by Dr. Papanicolaou in 1945, urinary cytology has proven to be a cheap, easily obtained, and accurate method in the detection of high-grade urothelial carcinoma. Despite readily agreed upon features of high-grade urothelial carcinoma, a reproducible, universally accepted reporting method has not been attained. The Paris System for Reporting Urinary Cytology was developed to bring about a standardized reporting system with specific diagnostic categories and clear cytomorphologic criteria for the reliable diagnosis of high-grade urothelial carcinoma. This paper sets out to review the utility of urinary cytology, the current understanding of urothelial carcinoma, and the diagnostic categories of The Paris System. We finish with a review of the current literature regarding implementation of The Paris System.